38‐4: Improving Performance of Curved TFT‐LCD with extreme curvature. Issue 1 (28th June 2021) - Yu, Liang; Zhao, Yongchao; Wang, Yanan; Song, Yanjun; Hsieh, Chung-Ching; Xiao, Juncheng; Zhao, Bin
Abstract : Flat TFT‐LCD with curved back light units(BLU) can obtain curved display effect. However, when the Flat TFT‐LCD bent with external force, there will be blocky black mura on both left and right sides, which makes the display effect worse. After analyzing a large number of blocky black mura phenomena and corresponding pre‐tilt angle data of curved TFT‐LCD, we summarized the quantitative relationship between the blocky black mura and pre‐tilt angle, and established a theoretical equation, which can be used to prejudge whether there will be blocky black mura after the TFT‐LCD bent, and to guide the improvement of blocky black mura.